Strategic management in Public Sector Organisations - Jibreal, Ahmed (Univerzita Pardubice, 2022)
The strategic management system in the local government is an efficient and effective way of implementing government and community plans. The strategic management system in the local government organizations in the municipalities of selected countries such as Finland, Norway, Switzerland, Germany, and Netherland are known for its history and stories. Nevertheless, such countries still face some challenges in the implementation of strategic management systems in the local governments as public sector organizations. The main aim of this research work was to examine how a selected branch of a public sector organization applies strategic management practice and what tools are used. Based on the analysis, a strategic approach will be defined that best corresponds to the characteristics of the public sector organization. A qualitative method approach was used where case study methods were to examine the strategic management practices applied to the local government organizations, the tools they used, and identify approaches that best correspond to the characteristics of the local governments as public sector organizations in the selected countries. Moreover, the analysis was done to examine how local government organizations applied strategic management practices and approaches and the tools they used. In the evaluation and discussion of the results based on the analysis of the research, it was found that the strategic management system has been successfully applied and implemented and was beneficial for the local government organizations of the selected countries. However, there were still challenges or obstacles that affect the strategic management system in the local government organizations in the municipalities of the selected countries.
Keywords: praktiky strategického řízení; veřejný sektor; řízení rizik; řízení lidských zdrojů; řízení výkonnosti systému; řízení znalostí; strategic management practices; public sector; risk management; human resource management; performance system management; knowledge management